ASME 2015 Noise Control and Acoustics Division Conference 2015
DOI: 10.1115/ncad2015-5911
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Low Noise Technologies Applied to a Full Scale Fuselage Mounted Nose Landing Gear

Abstract: The reduction of noise generated by aircraft at take-off and approach is crucial in the design of new commercial aircraft. Landing gear noise is significant contribution to the total noise sources during approach. The noise is generated by the interaction between the non-aerodynamic components of the landing gear and the flow, which leads to turbulence generated noise. This research presents results from the European Clean Sky funded ALLEGRA project. The project investigated a fullscale Nose Landing Gear (NLG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…To obtain a better understanding of the actual noise emissions of LG systems, wind-tunnel [12,[14][15][16][17] and aircraft flyover experiments [4,9] are typically performed. Whereas the first case offers more controlled flow conditions, it requires the LG model being tested to have a high level of geometric detail to represent the small-scale sound generating mechanisms of the gear [4,5] and it is difficult to replicate the exact conditions present at an aircraft in flight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain a better understanding of the actual noise emissions of LG systems, wind-tunnel [12,[14][15][16][17] and aircraft flyover experiments [4,9] are typically performed. Whereas the first case offers more controlled flow conditions, it requires the LG model being tested to have a high level of geometric detail to represent the small-scale sound generating mechanisms of the gear [4,5] and it is difficult to replicate the exact conditions present at an aircraft in flight.…”
Section: Introductionmentioning
confidence: 99%
“…The wind-tunnel experiments were performed under the European Clean Sky funded ALLEGRA (Advanced Low Noise Landing (Main and Nose) Gear for Regional Aircraft) project, coordinated by Trinity College Dublin. This project was developed to assess low-noise technologies applied to a full-scale NLG model [15,16] and a half-scale MLG model [17] of a regional aircraft. ALLEGRA consisted of a consortium of universities (Trinity College Dublin and KTH), an aeroacoustic wind-tunnel company (Pininfarina SPA), and European SME manufacturing and design partners (Eurotech and Teknosud) supported by a leading landing gear manufacturer (Magnaghi Aeronautica).…”
Section: Introductionmentioning
confidence: 99%
“…In practical cases, such as for aircraft take-off and landing where the flow speed varies, it is important to be able to predict these modes so that mitigation measures can be implemented for all modes excited. Recent research published from EU Green Regional Aircraft Clean Sky projects [19][20][21] have demonstrated success in the reduction of nose and main landing gear noise on full and half scale models with the use of low noise technologies. However, the wheel bays continue to be a significant noise source, and for approach and landing, velocities were found to radiate tones at both the Helmholtz resonance frequency of the nose landing gear wheel bay 22 and also at frequencies which were higher than the first, and most typically studied, depth mode for both the nose and main landing gear.…”
mentioning
confidence: 99%
“…There was a bias to radiate upstream for high-amplitude noise centered at 200 Hz, which was believed to be generated by the shear layer impinging on the drag stay and main strut, with contributions in this range from the doors and the steering pinion also. Given the high level of contribution from these components, deployable bay spoilers, such as examined by Dobrynski et al [9] in the RAIN project and Neri et al [40] in the ALLEGRA project, should be given serious consideration for production solutions. The pod gear concepts currently being investigated by NASA also offer great promise to attenuate these noise sources [41].…”
Section: Discussionmentioning
confidence: 99%